Android-based Mobile Wedding Organiser Application System for Yogyakarta Region - Muhammad Nurmansyah; Muhammad Fachrie (SEAN Institute, 2023)
A wedding organiser is a service that helps the bride-to-be and her family plan the wedding. Wedding organisers are often sought after by the public because they make it easier to plan a wedding party. During this time, booking a wedding party is done in the usual way: customers simply come to the house or call and ask if the Wedding Organizer package fits the budget and what facilities the Wedding Organizer has. The Wedding Organizer application system is built using Android-based technology. This Android based Wedding Organizer application system uses Android Studio and prototype. Email and password data will be connected to Firebase, data for registration and application login. The purpose of this research is to create an android based wedding organiser application system for the Yogyakarta area. The results of this research show that the wedding organizer application system can inform complete selection, wedding selection that includes (venue, tent, groom's wedding dress, bride's wedding dress), login and registration data is connected to Firebase database in real time, it is better to book in advance so that stock is available, payment via ATM transfer and confirmation via WhatsApp